2017
DOI: 10.1177/1476718x17705415
|View full text |Cite
|
Sign up to set email alerts
|

Head Start administrator and teacher perceptions of parental influence on preschool children’s nutrition education

Abstract: Parents play a significant role in molding their children’s nutrition knowledge and behavior. The purpose of the present study was to explore parental influence on preschooler’s nutrition education from the perspectives of North Carolina–based Head Start coordinators and teachers. Investigators conducted 63 in-depth, structured interviews with Head Start Health/Nutrition Coordinators (n = 31) and teachers (n = 32). Interviews were recorded in digital audio format and transcribed verbatim. Following a grounded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 45 publications
2
16
0
3
Order By: Relevance
“…The views of these individuals may be different from other HS teachers, even within eastern NC. With this being said, demographics are similar to those reported by other studies of HS teachers employed in NC (35,62,92) . Future research should explore individual, social and environmental influences of teachers' health behaviours in more diverse populations (e.g.…”
Section: Limitations and Strengthssupporting
confidence: 81%
“…The views of these individuals may be different from other HS teachers, even within eastern NC. With this being said, demographics are similar to those reported by other studies of HS teachers employed in NC (35,62,92) . Future research should explore individual, social and environmental influences of teachers' health behaviours in more diverse populations (e.g.…”
Section: Limitations and Strengthssupporting
confidence: 81%
“…Staff availability and allocation in the current study illuminate previously discovered challenges in teacher-to-child ratio (Coleman and Dyment, 2013) and reliance on volunteers to sustainably incorporate garden education (Ohly et al, 2016). Teachers in our study indicated having supportive administrative policies and support from parents (Stage et al, 2018) is critical to teacher success. Head Start encourages parent participation in the classroom, though teachers in the current study identified human resources as an intervening condition in their success.…”
Section: Discussionmentioning
confidence: 83%
“…(14). Sağlıklı beslenme davranışında çocukların en önemli rol modeli anneleri başta olmak üzere ebeveynleridir (15). Bu nedenle hem büyüdüğünde kronik hastalıklardan korunmasında hem de obezite ile mücadelede ebeveyn eğitimleri anahtar rol oynamaktadır (16).…”
Section: Discussionunclassified